1995
DOI: 10.1172/jci117871
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis induced by an anti-epidermal growth factor receptor monoclonal antibody in a human colorectal carcinoma cell line and its delay by insulin.

Abstract: Invest. 1995Invest. . 95:1897Invest. -1905

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
215
2
5

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(230 citation statements)
references
References 41 publications
8
215
2
5
Order By: Relevance
“…Treatment with mAb 225 also caused a reduction in the viability of DiFi cells by 45% compared to control cells in a timedependent manner ( Figure 1D). These results are consistent with our earlier report that mAb 225-inhibits the growth of DiFi cells (Wu et al, 1995). The observed induction of apoptosis by anti-EGFR mAb 225 was not a restricted phenomenon in DiFi cells with high EGFR (1.5 ± 2610 6 /cell) , as downregulation of EGFR by mAb 225 also induces apoptosis in another colorectal carcinoma FET cells (Figure 2A, upper two blots) which have low EGF binding sites [6.0610 3 , high a nity; 4.26610 4 , low a nity (Huang et al, 1992)].…”
Section: Mab 225 Induces Apoptosis In Colorectal Carcinoma Difi and Fsupporting
confidence: 94%
See 2 more Smart Citations
“…Treatment with mAb 225 also caused a reduction in the viability of DiFi cells by 45% compared to control cells in a timedependent manner ( Figure 1D). These results are consistent with our earlier report that mAb 225-inhibits the growth of DiFi cells (Wu et al, 1995). The observed induction of apoptosis by anti-EGFR mAb 225 was not a restricted phenomenon in DiFi cells with high EGFR (1.5 ± 2610 6 /cell) , as downregulation of EGFR by mAb 225 also induces apoptosis in another colorectal carcinoma FET cells (Figure 2A, upper two blots) which have low EGF binding sites [6.0610 3 , high a nity; 4.26610 4 , low a nity (Huang et al, 1992)].…”
Section: Mab 225 Induces Apoptosis In Colorectal Carcinoma Difi and Fsupporting
confidence: 94%
“…Earlier we showed that inhibition of EGFR tyrosine phosphorylation by anti-EGFR mAb 225 induces apoptosis in DiFi human colorectal carcinoma cells (Wu et al, 1995). In the present study, we investigate the mechanism of EGFR-mediated apoptosis in colorectal carcinoma cells by delineating the involvement of Bax.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…For example, stimulation of IL-3 or erythropoietin receptors provides both proliferation and survival signals to hematopoietic precursors (Boyer et al, 1992;Koury and Bondurant, 1988;Silva et al, 1996). Similarly, signaling through EGFR has been shown to promote cell cycle progression, di erentiation and survival of epithelial cells (Merlo et al, 1995;Wu et al, 1995). Blockade of EGFR signaling on benign and tumor epithelial cell lines with neutralizing antibodies directed against this receptor resulted in a cytostatic e ect with or without cell cycle arrest [ (Wu et al, 1995), and references therein.…”
mentioning
confidence: 99%
“…However, most cancers involve dysfunction of more than one PTK and crosstalk between their downstream signalling pathways. A therapeutic approach to address this issue involves co-targeting different PTKs (Wu et al, 1995;Ye et al, 1999;Moasser et al, 2001;Moulder et al, 2001;Lu et al, 2001;Chakravarti et al, 2002;Totpal et al, 2002;Camirand et al, 2002). For co-targeting approaches to be useful, careful consideration must be given to the choice of PTKs to be simultaneously blocked (Dancey and Sausville, 2003).…”
mentioning
confidence: 99%